The Effect of Financial Literacy on Consumptive Behavior: Self-Control as a Mediator - Marcella, Eka; Katsir, Ahmad; Fikri, Muhammad Ali; Kusuma, Desta Rizky (Proceedings Series on Social Sciences & Humanities, 2024)
Background: The situation faced by the younger generation today can affect their consumptive behavior. The level of literacy and self-control are some of the variables that can affect a person’s consumptive behavior. How financial literacy can affect a person’s consumptive behavior is the aim of this study. Method: To obtain research data, students of the Faculty of Economics and Business from various universities in the Special Region of Yogyakarta were given questionnaires. The data that has been obtained is then processed using the SPSS statistical tool. Results: Research shows that self-control has the ability to mediate the effects of financial literacy on consumptive behavior. Conclusion: Thus, it can be concluded that when one’s students have high financial knowledge, they are better able to control their consumptive behavior.